2021
DOI: 10.1186/s43094-021-00263-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of Leptadenia hastata (pers) decne and Momordica balsamina linn leaf extracts on lipid profile of streptozotocin-induced diabetic rats

Abstract: Background Changes in blood lipid level (dyslipidemia) play a central role in the onset and pathogenesis of macrovascular complications of diabetes mellitus. Traditional herbal healers commonly use anti-diabetic polyherbal formulations to provide a multi-therapeutic approach for the treatment of diabetes mellitus and its associated complications. The effect of the aqueous leaf extracts of Leptadenia hastata (pers) Decne, Momordica balsamina Linn and their combination on lipid profile of strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…2 , 10 Management/treatment options for DM range from lifestyle modification, exercise, insulin injection, and use of anti-DM drugs. 5 , 11 The biochemical basis of most anti-DM drugs involves inhibiting the catalytic activities of carbohydrate metabolizing enzymes, such as human pancreatic α-amylase (HPA) and α-glucosidase, which reduces blood sugar levels by suppressing carbohydrate digestion and glucose uptake, 3 , 8 making them the primary targets in controlling blood glucose in DM patients. 12 - 14 Studies have shown that inhibition of HPA is a better suppressor of postprandial hyperglycemia (PPHG) than α-glucosidase because it prevents excessive accumulation of maltose.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…2 , 10 Management/treatment options for DM range from lifestyle modification, exercise, insulin injection, and use of anti-DM drugs. 5 , 11 The biochemical basis of most anti-DM drugs involves inhibiting the catalytic activities of carbohydrate metabolizing enzymes, such as human pancreatic α-amylase (HPA) and α-glucosidase, which reduces blood sugar levels by suppressing carbohydrate digestion and glucose uptake, 3 , 8 making them the primary targets in controlling blood glucose in DM patients. 12 - 14 Studies have shown that inhibition of HPA is a better suppressor of postprandial hyperglycemia (PPHG) than α-glucosidase because it prevents excessive accumulation of maltose.…”
Section: Introductionmentioning
confidence: 99%
“…Decne, a member of the Asclepiadaceae family widely distributed in Tropical Africa, is one of the herbal remedies used by traditional healers to treat DM. 11 , 24 Furthermore, several experimental studies have reported the anti-diabetic activity of L hastata . 7 , 11 , 17 Other reported pharmacological and biological potentials of different parts of L hastata include antimicrobial, antiandrogenic, anti-inflammatory, and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations